Numerical simulation of the burger's equation - Intan Mastura Ramlee (Institute Mathematics Engineering, 2016)
The objectives of this study involved three main stages to discretized the Burgers' equation using E-EFDM and I-EFDM and to descretize modified Burgers' equation using E-EFDM; to verify the accuracy of the numerical solutions of Burgers' equation and modified Burgers' equation generated by E-EFDM and I-EFDM; to compare the accuracy of the numerical solution generated by E-EFDM and I-EFDM.